Tales from School Learning Disability and State Education after Administrative Reform - Wills, Rod.; Morton, Missy; McLean, Margaret; Stephenson, Maxine; Slee, Roger; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2014)
This is a book about the struggle of many New Zealand families to have their children with learning disabilities included in local community schools. It reviews the influences in the post war period that shaped the state response to the right of all children to attend school. Reflections from both education policy makers and parents of that time are included. The book also examines the more recent impact of neoliberal politics on education policy and the consequences experienced by families with school-aged children with disabilities who may well become ‘collateral damage in the enterprise of improving schools.’  After examining the families’ experience the book asks how inclusion can be fostered in schools and classrooms? Practitioners and academics present research findings that indicate alternative ways of thinking and acting that attest to more ethical and humane responses to human difference. Citizens, school personnel, politicians and policy makers should be challenged by the tales from school arising from attempts to achieve a ‘world class, inclusive education system.’ Cover photograph by Rod Wills, “Oratia District School”.
Keywords: Education; Education, general